Peran Guru dalam Memaksimalkan Literasi Teknologi pada Pembelajaran Bahasa Indonesia di Sekolah Dasar - Aprilia, Putri Nanda; Elya, Risqy Mutiara; Wulandari, Siska; Julianto, Indra Rasyid (Jurnal Cahaya Edukasi, 2025)
This study aims to reveal the role of teachers in maximising technological literacy in Indonesian language learning at primary schools. Teachers have the role of facilitator, motivator and evaluator in optimising the use of technology. Teachers are not only the deliverers of material, but also the mentors of students in utilising various devices and applications to improve language skills. By using the right media, students can increase their interest in reading, and the use of devices is very helpful in broadening students' knowledge. The use of media in Indonesian language learning creates an interesting atmosphere for students, so that they do not only focus on books or methods that are difficult to understand. In the world of education, there is a lot of use of technology as a means that can facilitate the learning process. This research uses a qualitative descriptive method with literature studies from various articles and books that support the research process.